Organizational Citizenship Behavior, What Does Really Matter? - Mochamad Soelton; Eko Tama Putra Saratian; Aji Erlangga; Harefan Arief; Yeni Kamalia; Tantri Yanuar Rahmat Syah; Irfan Noviandy Aulia (Forum Inovasi Bisnis dan Manajemen, 2021)
Human resources management is currently a necessity and is no longer an option if a company wants to grow. Human Resources is very important in an organization, because the effectiveness and success of an organization is very dependent on the quality and performance of the human resources that exist in the organization. This study aims to examine and analyze the influence of Political Organization, Organizational Climate, and Organizational Culture on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an intervening variable at PT. Pegadaian Indonesia (PERSERO). The object of this research is the employees as many as 80 respondents. The approach used in this research is the Component or Variance Based Structural Equation Model with Smart-PLS analysis tools. The results showed that the Political Organization had no significant effect on Job Satisfaction on the employees, Organizational Climate has a significant positive effect on Job Satisfaction, Organizational Culture has a significant positive effect on Job Satisfaction, Political Organizational significant positive effect on Organizational Citizenship Behavior on employees, Organizational Climate has a significant positive effect on Organizational Citizenship Behavior for employees, Organizational Culture significantly positive effect on Organizational Citizenship Behavior on employees, Job Satisfaction has a significant positive effect on Organizational Citizenship Behavior.